THE NEED FOR MALOCCLUSION TREATMENT AT 12-14 YEARS BASED ON IOTN-AC IN SOUTH DAHA DISTRICT - Sherly Nuralisa Sinay; Diana Wibowo; Aulia Azizah (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: Malocclusion is a deviation that occurs in the teeth or malrelation of the dental arch that is not within the normal range. The prevalence of malocclusion in Indonesia is very high at 80%. Malocclusion cases in South Kalimantan Province with the age group of 12-14 years were 15.6%. The malocclusion index that the researcher used in this study was the Index of Orthodontic Treatment Need (IOTN) using the Aesthetic Component (AC). Purpose: To identify the level of need for malocclusion treatment at the age of 12-14 years based on IOTN-AC in South Daha District. Material and Methods: This study uses descriptive method with cross-sectional approach. The number of samples is 110 samples. Data analysis was carried out by using descriptive analysis. Result: The highest level of malocclusion treatment needs at the age of 12 years was score 3 by 31% and those who needed more treatment were male. The level of malocclusion treatment needs the most at the age of 13 years is score 2 by 36% and the male gender is the most in need of treatment. The level of malocclusion treatment needs the most at the age of 14 years is score 2 by 29% and the female gender is the most in need of treatment. Conclusion: The highest level of malocclusion treatment needs at the age of 12-14 years in South Daha District is score 2 (not requiring treatment) of 31% and those who need more treatment are male in South Daha District.Keywords: Adolescent, IOTN-AC, Malocclusion